2009
DOI: 10.1016/j.micromeso.2008.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Nanotemplated lead telluride thin films

Abstract: a b s t r a c tDirect lyotropic liquid crystalline templating has been successfully applied to produce nanostructured IV-VI semiconductor PbTe thin films by electrodeposition both on gold and n-type (1 0 0) silicon substrates. The PbTe films were characterized by transmission electron microscopy, X-ray diffraction and polarized optical microscopy and the results show that the films have a regular hexagonal nanoarchitecture with a high crystalline rock salt structure and exhibit strong birefringence. The optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…So far, only a few studies have been reported on Au-PbTe interfaces, mainly prepared by electrodeposition of lead telluride films/large crystals on gold substrates, and aiming at assessing the epitaxial relationships between the two materials and their optical properties. 30,31 Our initial drive was therefore to explore the possibility to grow metallic gold domains on top of the PbTe nanocrystals, in analogy with the several reported cases of noble metal nucleation on selected regions of cadmium chalcogenides nanocrystals [32][33][34][35][36][37] and also on PbS 38,39 (it is worth to point out that Au-PbS and Au-PbSe nanocrystal heterostructures have been prepared also starting from Au nanoparticles as catalysts 40 ). However, a recent work on the reaction of solutions containing Au(III) species with PbS nanocrystals has highlighted that lead chalcogenides might often react differently towards Au(III) than the corresponding cadmium chalcogenides.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few studies have been reported on Au-PbTe interfaces, mainly prepared by electrodeposition of lead telluride films/large crystals on gold substrates, and aiming at assessing the epitaxial relationships between the two materials and their optical properties. 30,31 Our initial drive was therefore to explore the possibility to grow metallic gold domains on top of the PbTe nanocrystals, in analogy with the several reported cases of noble metal nucleation on selected regions of cadmium chalcogenides nanocrystals [32][33][34][35][36][37] and also on PbS 38,39 (it is worth to point out that Au-PbS and Au-PbSe nanocrystal heterostructures have been prepared also starting from Au nanoparticles as catalysts 40 ). However, a recent work on the reaction of solutions containing Au(III) species with PbS nanocrystals has highlighted that lead chalcogenides might often react differently towards Au(III) than the corresponding cadmium chalcogenides.…”
Section: Introductionmentioning
confidence: 99%